The influence of human resource planning and supervision functions on fresh fruit bunch (FFB) production performance at PT. Perkebunan Nusantara IV Regional VI Aceh - Hakim Susanto; Hazmanan Khair (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of human resource planning and supervision functions on Fresh Fruit Bunches (FFB) production performance at PT. Perkebunan Nusantara IV Regional VI Aceh. The study used a quantitative method by distributing questionnaires to 30 employees as respondents. Data analysis was carried out using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results showed that human resource planning and supervision functions had a positive and significant effect on FFB production performance, both partially and simultaneously. Simultaneously, both variables had a significant influence on production performance with an F-count value of 327.507 and a significance level of less than 0.05. The coefficient of determination (R²) value of 0.960 indicated that 96.0% of the variation in FFB production performance could be explained by human resource planning and supervision functions, while the remaining 4.0% was influenced by other factors outside the study. These findings indicate that the implementation of effective human resource planning and supervision functions can improve the company's production performance.